Biblical happiness and baptismal identity - Van der Merwe, Izak Johannes (Stellenbosch Theological Journal, 2016)
In this essay the author makes a theological contribution to the happiness discourse, by i) exploring the etymology of some terms used for happiness in the Old and New Testament, by ii) valuing the contribution of Ellen Charry on biblical happiness as “Asherism” and iii) emphasizing the sacraments, in particular baptism, as identity marker, constituting a calling to a flourishing life, which includes being a flourishing agent enabling the flourishing of others and God’s creation.